Fibrous dysplasia of maxillary sinus-our experience - Jayakumar, Varunkumar; Jaiswal, Shubhalaxmi Atmaram (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
The fibrous dysplasia is a benign bone disease, of slow growth and unknown etiology. The involvement of the craniofacial skeleton is not uncommon and generally produces facial asymmetries. Presenting case series with fibrous dysplasia occupying the entire maxillary sinus confirmed with the radiological investigations. The patients were clinically examined and with proper explained consent patients were worked up for excision of the involved lesion. Coronal sections of paranasal sinuses was done and diagnosis was confirmed. Patients were posted for recontouring of fibrous dysplasia and achieved cosmetic refigurement. The surgical treatment remains as the main therapeutic approach and the postoperative follow-up is necessary due to this condition recurrent nature.